Pengaruh Penambahan Tepung Lidah Buaya (Aloe Vera) pada Pakan terhadap Konsumsi Pakan, Bobot Badan Akhir dan Presentase Karkas Ayam Broiler - Arum Dharani, Maytria; Eka Wati, Novi; Suhadi, Miki (JDP: Jurnal Dunia Peternakan, 2023)
Good carcass quality requires an increase in broiler productivity. Increasing the productivity of broiler chickens requires good feed quality for growth. The purpose of this study was to determine the effect of the addition of Aloe vera flour on feed consumption, final weight and carcass percentage of broiler chickens. Variables to be observed in the study Effect of Addition of Aloe vera Flour in Feed on Feed Consumption, Final Body Weight and Carcass Percentage of Broiler Chickens. Maintenance of broiler chickens was carried out for 28 days, 1 week old broiler chickens were treated P0 = 100% ration without additional Aloe vera flour, P1 = ration + 0.25% Aloe vera flour (2.5 g/kg ration), P2 = ration + 0.5% Aloe vera flour (5 g/kg ration), P3 = ration + 0.75% Aloe vera flour (7.5 g/kg ration). Based on the results of the study it can be concluded that the addition of Aloe vera flour up to a dose of 0.75% had a significant effect (P<0.05) on reducing feed consumption, but the addition of Aloe vera flour up to a dose of 0.75% had no significant effect on the final body weight. and carcass percentage.